The Historian's Eye : Photography, History, and the American Present - Jacobson, Matthew Frye, 1958- (Book collections on Project MUSE., 2019)
"Between 2009 and 2013, as the nation contemplated the historic election of Barack Obama and endured the effects of the Great Recession, Matthew Frye Jacobson set out with a camera to explore and document what was discernible to the 'historian's eye' during this tumultuous period. Having collected several thousand images, Jacobson began to reflect on their raw, informal immediacy alongside the recognition that they comprised an archive of a moment with unquestionable historical significance. This book presents 100 images alongside Jacobson's recollections of their moments of creation and his understanding of how they link past, present, and future"--